The Impact of Employee Creativity and Transformational Leadership on Innovation Work Behavior in the Banking Sector - Arsyad, Irwan Eka Wijaya (RSF Conference Series: Business, Management and Social Sciences, 2024)
This study examines the role of transformational leadership in promoting an innovative work environment and work behavior in the rural bank Industry. The research was conducted at Bank UMKM, a company that holds a significant market share in the region’s rural bank industry. A survey was conducted with 671 employees across the company’s branches. The findings reveal that all hypotheses, except Hypothesis 1, were accepted. Transformational leadership positively affects employee creativity, indirectly influencing innovation work behavior. Additionally, the relationship between transformational leadership and innovative work behavior is strengthened by the presence of trust in supervisors. Although transformational leadership did not have a direct impact on innovative work behavior, the research highlights the significance of cultivating an inventive work environment and the influence of trust in supervisors in encouraging innovation within the rural bank business.